The Secret In The Old Attic - Keene Carolyn; Carolyn Keene (New York Carolyn Keene, 1944)
Nancy hunts for missing, valuable music manuscripts hidden by a deceased soldier, Philip March, to save his family from financial ruin.
Keywords: Carolyn Keene centers on the conduct of life through the lens of tenacity, compassion, and professional diligence, particularly in the face of economic hardship; centers on the value of hard work, tenacity, and courage in uncovering the truth